Reproduction aspects of the genus Characidium Reinhardt, 1867 (Crenuchidae, Characidiinae) in the Ribeirão Grande system, serra da Mantiqueira, southeastern Brazil- DOI: 10.4025/actascibiolsci.170 - Braga, Francisco Manoel de Souza (2006)
Aspects of the reproductive biology of Characidium lauroi and C. alipioi were described. Maturation of the gonads was divided into four stages, and the distribution of the stages in an annual cycle was reported. The Characidium lauroi has a higher spawning period in the spring, and the C. alipioi, in the summer. The size at sexual maturity of the Characidium lauroi was about 4.2 cm total length for males and 5.1 cm for females; as for the C. alipioi, males were about 6.2 cm total length and females were about 5.8 cm. The gonadosomatic index values indicated the stage of maturity and were determined for each species and sex. The high values observed in October for Characidium lauroi males and females mark the maturation peaks in both sexes, and the peaks coincided with the spawning period. As for C. alipioi, the peaks were in February and also coincided with the spawning period.